Notoginsenoside R1–Induced Neuronal Repair in Models of Alzheimer Disease Is Associated With an Alteration in Neuronal Hyperexcitability, Which Is Regulated by Nav - Hu, Tao; Li, Shan; Liang, Wen-Qi; Li, Shan-Shan; Lu, Min-Nan; Chen, Bo; Zhang, Li; Mao, Rui; Ding, Wan-Hai; Gao, Wen-Wei; Chen, Shi-Wen; XiYang, Yan-Bin; et al. (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s Disease which is characterized by a progressive cognitive deficit, may be associated with the aberrant hyperexcitability of neuronal network. Notoginsenoside R1 (R1), a major activity ingredient from Panax notoginseng (PNS), has demonstrated some changes of neuronal plasticity in networks and induced neuroprotective effects in brain injuries result from various disorders, but the mechanisms are still not well understood. In the present study, we aim to explore the possible neuroprotective effects induced by R1 in AD model and the mechanisms underlying. The treatment with R1 significantly improved the learning and memory functions and redressed neuronal hyperexcitability in APP/PS1 mice by altering the numbers and/or distribution of the members of voltage-gated sodium channels (Nav). Moreover, we determined whether R1 contributed to the neuronal excitability regulation in Aβ-42-injured cells. Results of our study demonstrated that treatment with R1 rescued Aβ1-42-induced injured neurons by increasing viability of the cells. R1-induced alleviation in neuronal hyperexcitability might be associated with the reduced Navβ2 cleavage and thus partially reversed the abnormal distribution of Nav1.1. These results suggested that R1 played a vital role in the recovery of Aβ1-42-induced neuronal injury and hyperexcitability which is regulated by Nav proteins. R1 may be a promise candidate for AD treatment.